THE EFFECT OF 200 GRAM AND 500 GRAM RED DRAGON FRUIT JUICE (Hylocereus polyhizus) IN INCREASING OF HEMOGLOBIN LEVEL ADOLESCENT GRILS IN SMA NEGERI I BANGUNTAPAN BANTUL 2020 - Wahyuningsih, Melania; Khasanah, Nur; Widodo, Christanty DN (Jurnal Keperawatan Respati Yogyakarta, 2021)
Teenage girls are prone to suffer from anemia because of a lot of blood loss during menstruation. Iron deficiency can cause them to be weak, and make them difficult to concentrate, because hemoglobin cannot carry enough protein and oxygen. Dragon fruit contains a lot of iron (Fe) to form red blood cells, and vitamin C can accelerate the absorption of iron for the body. To determine the effect of giving red dragon fruit juice (Hylocereus Polyrhizus) on the increase of hemoglobin in the post-menstrual adolescent girls at SMA Negeri 1 Banguntapan. The research design was a quasy experiment using pre- and post-test nonequivalent control group design. The study population consisted of 54 people. The study sample comprised 18 people consisting of 9 control groups and 9 intervention groups. Sampling was conducted with purposive sampling. The data collected were the hemoglobin levels of Grade XI of Social Science students at SMAN 1 Banguntapan, Bantul. Dragon fruit juice 200 grams is effective for increasing hemoglobin levels adolecent girls in SMA Negeri I Banguntapan Bantul p value 0.011 (p value <Î± (0.05).Dragon fruit juice 500 gram is effective for increasing hemoglobin level adolecent girls in SMA Negeri I Banguntapan Bantul p value 0.009 (pvalue <Î± (0.05).There was no significant difference on the dragon fruit juice 200 gram and 500 gram in increasing hemoglobin level adolecent girls in SMA Negerei I Banguntapan Bantul p value 0.280 (P value > 0.05) Keywords: Dragon Fruit Juice; Hemoglobin Levels; Adolescent Girls